1994
DOI: 10.1002/1097-0142(19940701)74:1<38::aid-cncr2820740108>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous heparin treatment increases survival in small cell lung cancer

Abstract: Background. A positive influence of anticoagulant treatment in small cell lung cancer (SCLC) has been sug gested by experimental and clinical data. Methods. In a multicenter clinical trial, 277 patients with SCLC were randomized either to receive or not to receive subcutaneous heparin injections for 5 weeks at effective doses, which were monitored by blood coagulation tests. All patients received one of the two chemotherapy regimens studied in this trial, for eight courses in the case of patients with complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(156 citation statements)
references
References 22 publications
7
146
0
3
Order By: Relevance
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17). However, heparin therapy can be difficult to manage on an outpatient basis and is associated with some complications.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17). However, heparin therapy can be difficult to manage on an outpatient basis and is associated with some complications.…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…In addition, anticoagulant drugs warfarin and/or heparin were used in animal tumor models with positive results (Ornstein and Zacharski, 1999). Controlled clinical trials using these drugs were initiated and have produced encouraging outcomes, warfarin and heparin both prolonged the length of survival of patients with small cell carcinoma of the lung and malignant melanoma (Lebeau et al, 1994;Thornes et al, 1994). These findings suggest a potential role for thrombin inhibitors in cancer therapy.…”
Section: How Activation Of Par-1 Contributes To Melanoma Metastasismentioning
confidence: 99%
“…Two trials (FAMOUS and MALT) previously studied the effect of unfractionated heparin (UFH) [4] or low molecular weight heparin (LMWH) [5] in patients with small cell lung cancer. In both of these studies, a statistically significant survival advantage was observed in patients randomized to chemotherapy plus UFH or LMWH relative to patients who received chemotherapy alone.…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%
“…The effect of heparin on tumors includes interference with cancer-induced hypercoagulation, cancer cell proliferation, degradation of the extra-cellular matrix (involving the heparan sulfate chains of cell surface and extracellular matrix proteoglycans), angiogenesis, selectin-mediated binding of platelets and cancer cells, growth factors and their receptors, hepara- nase, tumor progression, and metastasis [13,14] . Heparin was proposed to have a role in maintaining the effects of chemotherapeutic drugs, as both UFH and LMWH have been shown to act as chemotherapy sensitizers [4,5] . In our evaluation of the influence of heparin on tumor cell proliferation, cell cycle and apoptosis, we found that it could inhibit proliferation of PC-3M tumor cells and arrest them in the G 0 /G 1 phase.…”
Section: Effect Of Heparin On Brdu Incorporation and Ki67 Expression mentioning
confidence: 99%